Adaptive antenna array control in the presence of interfering signals with stochastic arrivals assessment of a GA-based procedure. - Sacchi, C. (IEEE Transactions on wireless communications)
In this letter, a real-world working case of interfering signals coming to an antenna array with random arrivals modeled as a Poisson process is considered. A procedure based on a suitable genetic algorithm for adaptive array control is assessed by means of numerical simulations. Selected results clearly demonstrate the effectiveness and flexibility of the proposed procedure.